Galanthamine biosynthesis in plant in vitro systems. Issue 6 (November 2014) - Berkov, Strahil; Ivanov, Ivan; Georgiev, Vasil; Codina, Carles; Pavlov, Atanas
<x xml:space="preserve">Abstract</x> The Amaryllidaceae alkaloid galanthamine (Gal) is a long‐acting, selective, reversible, and competitive acetylcholinesterase inhibitor used for the treatment of early‐ to mid‐stage Alzheimer's disease, poliomyelitis, and other neurological diseases. Currently, Gal is produced by extraction from plants such as daffodils (Narcissus cultivar Carlthon), snowflake (Leucojum aestivum), "red‐tubed lily" (Lycoris radiata), and Ungernia victoria, and alternatively by chemical synthesis. Due to the increased demand by the generic pharmaceutical companies and the limited availability of plant sources, the biosynthesis of Gal by plant in vitro systems has been considered as an alternative approach for its sustainable production. The present article reviews the state of the art of in vitro Gal biosynthesis including growth regulators, medium components, culture conditions, elicitation, and bioreactor systems. It may be used as a starting point for further studies in this area leading to a progress in biotechnological production of this valuable alkaloid.